The power of microsatellite markers and AFLPs in revealing the genetic diversity of Hashemi aromatic rice from Iran - Alireza Tarang; Anahita Bakhshizadeh Gashti (Journal of Integrative Agriculture, 2016)
Hashemi, a popular aromatic rice among Iranians, is famous for its fragrance and taste. Such features are major reasons for its higher price compared to non-aromatic varieties available in Iran. Therefore, the knowledge of genetic diversity of this profitable crop is a fundamental ineterst for plant breeders in future breeding programs. In the present research, genetic diversity among 35 genotypes of Hashemi aromatic rice (Oryza sativa L.) from Guilan and Mazandaran provinces of Iran was estimated using simple sequence repeat (SSR) and amplified fragment length polymorphism (AFLP) markers. Out of 21 SSR and 12 EcoRI-MseI AFLP marker combinations, only 16 SSRs and 10 AFLPs exhibited polymorphic patterns while others were monomorphic. The 10 AFLP primer combinations produced a total of 142 of bands and 20 were polymorphic (14.08%). Moreover, 40 out of 47 bands amplified with 16 SSR markers showed polymorphism (85.1%). The average number of alleles identified by SSR primers was 2.56 alleles per locus with a range of 2 to 4. The average value of polymorphic information content (PIC) was 0.393 and 0.468 for AFLP and SSR markers, respectively. However, the genetic similarity values ranged from 0.26 to 1 for SSRs and 0.21 to 1 for AFLPs. Later, a unweighted pair group method with arithmetic mean (UPGMA) dendrogram was generated and genotypes were clustered into four groups with SSRs at similarity coefficient of 0.55 while AFLPs clustered them into six groups at similarity coefficient of 0.41. Cluster analysis revealed a narrow genetic diversity and low correlation between geographical differentiation and genetic distance within cultivars.